Новий локалітет Spiranthes spiralis (Orchidaceae) в Україні - Кузярін, О.Т. (Український ботанічний журнал, 2014)
Сообщается о находке нового локалитета Spiranthes
spiralis (L.) Chevall. (Orchidaceae) в августе 2012 г. на
залежи вблизи г. Львова. Дана детальная характеристика
нового местонахождения вида. Обобщена информация
о распространении S. spiralis в Украине. Уточнен
природоохранный статус вида. A new locality of Spiranthes spiralis (L.) Chevall. (Orchidaceae)
in Ukraine is reported. It was found on the fallow field near Lviv
city in August, 2012. Detailed characteristic of the new habitat
of the species is given. Information on distribution of S. spiralis
in Ukraine is summarized. The conservation status of the species
is specified.